Mapping Magnetic Properties of Spintronic Materials Using a First Principles Framework - Dalum, mit Doan (Trinity College Dublin. School of Physics. Discipline of Physics, 2025)
In recent years, the field of spin electronics (Spintronics) has made significant advances in novel magnetic data storage and processing technologies in terms of energy efficiency, non-volatility, and compact design. While spintronic devices offer promising prospects, they face a persistent challenge known as the "THz-gap," which refers to the limited frequency range that current THz radiation sources can operate within. Computational simulation techniques have emerged as a pivotal tool for bridging this gap, enabling researchers to model and optimize complex nanoscopic devices based on stacks of novel low-moment ferri- or antiferro-magnetic materials (having high natural frequency) with precision, thereby facilitating advancements in this strategic field. This approach not only aids in overcoming existing technological barriers but also contributes significantly to the realization of practical applications based on theoretical predictions. In this thesis, we present a systematic approach developed to design a protocol based on ab initio theoretical methods for exploring the potential of various novel low-moment ferrimagnetic and antiferromagnetic materials, as well as topical ferromagnetic Heusler compounds, as functional elements in spintronic devices. Specifically, we aim to map magnetic properties using density functional theory (DFT) and employ state-of-the-art materials science techniques to address the limitations of standard DFT, and comparing the effectiveness of different implementations of Hubbard corrections in describing the low-moment ferrimagnet Mn3Ga. We then analyze magnetocrystalline anisotropy energies to assess magnetic domain stability in selected materials, including Mn3Ga (a low-moment ferrimagnet), CrSb (an altermagnet), and CuMnAs (an antiferromagnet). Finally, we develop a practical scheme for calculating Heisenberg exchange parameters using the spin-spiral approach. These results allow us to construct a simplified classical spin Hamiltonian to study the thermodynamic behavior of promising low-moment magnetic materials. Additionally, we compared our findings against existing literature on standard ferromagnets (such as the 3d transition metals) and a range of topical Heusler compounds, including Cu2MnAl, Pd2MnSn, Ni2MnGa, Ni2MnSn, NiVSb, and NiVSn. This comparison enables us to evaluate the performance of fully self-consistent versus magnetic force theorem-based approaches for extracting Heisenberg exchange parameters, highlighting their respective advantages and limitations within the widely used VASP code-the workhorse of ab initio electronic structure calculations in materials science-. Since there are only a few such methods currently exist in the literature for extracting these parameters from first principles, and most rely on private codes used within small research communities, by demonstrating a practical scheme available within VASP, we aim to make this valuable theoretical tool more accessible to the broader research community in magnetism and spintronics.
APPROVED
Keywords: Magnetic Properties of Spintronic Materials